The sensitivity of laboratory tests assessing driving related skills to dose-related impairment of alcohol: A literature review. (April 2016) - Jongen, S.; Vuurman, E.F.P.M.; Ramaekers, J.G.; Vermeeren, A.
Highlights: Alcohol can be used as a benchmark of impairment for other drugs. Sensitivity and reliability of tests measuring driving related skills were reviewed. A cued go/no-go task and a divided attention test were reliably sensitive. Simulated driving tests should be compared head to head with actual driving tests. Abstract: Laboratory tests assessing driving related skills can be useful as initial screening tools to assess potential drug induced impairment as part of a standardized behavioural assessment. Unfortunately, consensus about which laboratory tests should be included to reliably assess drug induced impairment has not yet been reached. The aim of the present review was to evaluate the sensitivity of laboratory tests to the dose dependent effects of alcohol, as a benchmark, on performance parameters. In total, 179 experimental studies were included. Results show that a cued go/no-go task and a divided attention test with primary tracking and secondary visual search were consistently sensitive to the impairing effects at medium and high blood alcohol concentrations. Driving performance assessed in a simulator was less sensitive to the effects of alcohol as compared to naturalistic, on-the-road driving. In conclusion, replicating results of several potentially useful tests and their predictive validity of actual driving impairment should deserve further research. In addition, driving simulators should be validated and compared head to head to naturalistic driving in order to increase construct validity.